Advanced Triaxial Testing of Soil and Rock 1988
DOI: 10.1520/stp29090s
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Reconstituted Sand Specimens

Abstract: Review and assessment of sand sample preparation techniques from both theoretical and experimental viewpoints are presented. Sample densities obtained by air pluviation are shown to be sensitive to rate of pouring and drop height. Terminal velocity is reached at a very small drop height, and homogeneous samples of the same initial density tend to be formed by pluviation of uniform sand in water. Uniformly dense samples obtained by vibration of loose pluviated samples show no detectable difference in behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 11 publications
0
56
0
Order By: Relevance
“…Naughton (2002) showed that the initial relative density of the testspecimens is not affected by the diameter of the depositing pipe and that the test-specimen can be reproduced to within Ϯ10% of a desired target relative density. The variation in the initial relative density of the testspecimen is larger than the Ϯ2% reported by Vaid & Negussey (1988) who also used a wet-pluviation sample preparation technique. The difference in the magnitude of this error occurs as a consequence of the smaller test-specimen size used in the present study and the limitations in determining the initial dimensions of the test-specimen to sufficient resolution.…”
Section: Sample Preparation Methodsmentioning
confidence: 58%
“…Naughton (2002) showed that the initial relative density of the testspecimens is not affected by the diameter of the depositing pipe and that the test-specimen can be reproduced to within Ϯ10% of a desired target relative density. The variation in the initial relative density of the testspecimen is larger than the Ϯ2% reported by Vaid & Negussey (1988) who also used a wet-pluviation sample preparation technique. The difference in the magnitude of this error occurs as a consequence of the smaller test-specimen size used in the present study and the limitations in determining the initial dimensions of the test-specimen to sufficient resolution.…”
Section: Sample Preparation Methodsmentioning
confidence: 58%
“…However, this variation was significantly larger than the 0.6 % variation in the void ratio of Ottawa sand specimens prepared using a similar technique and tested in the University of British Colombia (UBC) HCA (Vaid and Negussey, 1988). The UBC specimens were 51.0 mm inner radius, 76.0 mm outer radius, and 302 mm high.…”
Section: Analysis Of Error In the Void Ratiomentioning
confidence: 87%
“…Most commonly used sample preparations are air pluviation, water pluviation, slurry deposition, dry deposition, and moist tamping. The major factors which affect the relative density of air pluviated sands are height of particle drop (Vaid and Negussey, 1988) and rate of deposition (Miura and Toki 1982). Air Pluviation of well-graded sand is not as successful as air pluviation of well-sorted sand.…”
Section: Testing Programmentioning
confidence: 99%